Life without plastic : the practical step-by-step guide to avoiding plastic to keep your family and the planet healthy - Plamondon, Chantal; Sinha, Jay (Page Street Publishing Co., 2017)
After the birth of their son, Jay Sinha and Chantal Plamondon set out on a journey to eliminate plastic baby bottles as the Canadian government moved to ban BPA. When they found it was difficult to procure glass baby bottles, Jay and Chantal made it their mission to not only find glass and metal replacements for plastic, but to make those products accessible to the public as well. While plastic has its uses in technology, the medical and industrial sectors and some products around the home, single-use plastics may release chemicals when they come in contact with food and water. These disposable plastics are commonly used to package food and drinks as well as personal care and cleaning products. Jay and Chantal show readers how to analyze their personal plastic use, find alternatives and create easy replacements in this step-by-step guide. Get your family healthier, spread consciousness and radiate positive plastic-free energy by taking action to help the environment.